The varied functions of the giant muscle scaffold protein obscurin - Di Paola, James Novac; Schöck, Frieder (Frontiers in Cell and Developmental Biology, 2026)
Obscurin is a giant protein encoded by the OBSCN gene in human myocytes, known for its roles in sarcomere organization, elasticity, stretch response, and myofibrillogenesis. Alternative splicing of OBSCN generates variants with distinct properties and localizations, including small kinase variants in mammals. Investigating obscurin-like 1 (Obsl1) and striated muscle-enriched protein (SPEG), the other members of the obscurin family in higher eukaryotes, has allowed a better understanding of obscurin family function in the sarcoplasmic reticulum, mitochondrial fragmentation, and kinase domain regulation. Obscurin’s association with ankyrin isoforms in vertebrates demonstrates participation in membrane and cytoskeletal organization within muscle tissues while binding to myosin actively contributes to the formation and maintenance of the sarcomeric contractile apparatus and the M-line. The Rho-guanine nucleotide exchange factor (RhoGEF) domain of obscurin suggests a role in activating small GTPases and autoregulation. Obscurin also binds titin, indicating a dynamic function in monitoring sarcomere extension and relaying cues in muscle remodeling. Obscurin and titin can further form a tertiary complex with myomesin in vertebrates, reinforcing its importance in M-line assembly and sarcomeric organization. Beyond muscle tissue, obscurin is expressed and plays additional roles in various other organs, including skin, brain, kidney, liver, spleen, and lung. Potential tumor-suppressing properties have been revealed through OBSCN lncRNAs and epigenetic regulation. This review aims to provide a comprehensive overview of obscurin’s molecular functions and interactions by discussing the effects of its differential expression and its interactions with binding partners, along with the differences and similarities between vertebrate and invertebrate obscurin.